Risk factors associated with the severity of traffic accident victims in Magelang District - Sabono, Julianti Jeanette; Kusnanto, Hari (BKM Public Health and Community Medicine, 2021)
Purpose: This study aimed to analyze risk factors affecting the severity of traffic accident victims in Magelang District and identify accident locations within the Magelang District Police Department's work area. Methods: This observational study employed a cross-sectional design using secondary data. The subjects included all individuals involved in road traffic accidents as recorded in the 2018 Accident Report of the Magelang District Police Department. The independent variables were age, sex, time of occurrence, day of occurrence, road type, natural conditions, type of collision, and type of vehicle. Data analysis was conducted using logistic regression and Quantum GIS 2.18. Results: Age over 56 years was significantly associated with the severity of traffic accident victims (95% CI: 1.275–5.215). Additionally, single motorbike collisions were also found to influence injury severity (95% CI: 1.438–1167.166). Spatial analysis revealed clusters of accident locations along several major roads, including the Yogyakarta–Magelang Road, Babak Mungkid Road, Soekarno Hatta Road, Semarang–Magelang Road, Secang Road, and Salam–Bener Road. Conclusion: There was a statistically significant relationship between age and the type of collision, as well as the severity of the accident victims. Multisectoral cooperation is expected to enhance the socialization of driving behavior within the community, provide adequate road facilities, and regulate traffic flows effectively to reduce the incidence and fatalities from traffic accidents.